Touch DNA viability on various substrates from different shedder levels - Saamia, Vira; Yudianto, Ahmad; Nurjayadi, Muktiningsih; Novitasari (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Touch DNA samples are frequently discovered at crime scenes, including those found at the scene, on the victim, with the suspect, or on objects related to the incident. This study aimed to investigate 3 key factors affecting touch DNA samples: the characteristics person that shed the DNA, surfaces variants where the DNA was deposited, and different sampling methods effectiveness that influence DNA quantity, quality, and detection. METHODS 9 participants grouped into high, intermediate, and low shedder levels simultaneously tied 2 types of ropes, non-porous and porous. The first person will hold a rope for 5 min then pass it to the second person to hold on the same spot for another 5 min. DNA was collected from each rope using the double swab and tape-lift method, extracted, and quantified using real-time polymerase chain reaction (PCR). Touch DNA profile at 20 short tandem repeat loci was amplified in PCR system and detected on capillary electrophoresis. RESULTS Type of substrate (p = 0.97) or sampling method (p = 0.053) used for touch DNA collection did not significantly impact the DNA yield or profiling outcomes. A notable difference (p<0.001) was found in DNA quantity between high, intermediate, and low shedders, regardless of the substrate or method used. CONCLUSIONS Individual shedder level has a greater influence on the results of touch DNA analysis regarding the DNA quantity and profiling quality than substrate type and sample procedure.